2016
DOI: 10.1016/j.jaut.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-10 is a target of T and B cell responses that correlate with synovial pathology in patients with antibiotic-refractory Lyme arthritis

Abstract: Infection-induced autoimmunity is thought to be a contributing factor in antibiotic-refractory Lyme arthritis, but studies of autoimmunity have been hindered by difficulty in identifying relevant auto-antigens. We developed a novel approach that begins with the identification of T cell epitopes in synovial tissue using tandem mass spectrometry. Herein, we identified an immunogenic HLA-DR-presented peptide (T cell epitope) derived from the source protein matrix metalloproteinase-10 (MMP-10) from the synovium of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 95 publications
(128 reference statements)
1
68
0
2
Order By: Relevance
“…Similarly, among the five LA patients, at least one unique immunogenic HLA-DR-presented peptide was identified in each of three patients (LA1, LA4, and LA5). 2224 Four of the six immunogenic peptides were identified by consensus match, and two were identified by manual inspection of sequences identified by only one program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, among the five LA patients, at least one unique immunogenic HLA-DR-presented peptide was identified in each of three patients (LA1, LA4, and LA5). 2224 Four of the six immunogenic peptides were identified by consensus match, and two were identified by manual inspection of sequences identified by only one program.…”
Section: Resultsmentioning
confidence: 99%
“…The peptides found to be immunogenic were derived from the source proteins endothelial cell growth factor (ECGF), 22 apolipoprotein B-100 (apoB-100), 23 matrix metalloproteinase-10 (MMP-10) 24 in LA; from annexin A2 in both RA and LA, 25 and from N -acetylglucosamine-6-sulfatase and filamin A in RA. 26 The MS/MS spectra and peptide sequences determined for these autoantigens are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…We have developed an approach for antigen detection in chronic inflammatory arthritides, in which HLA-DRpresented peptides (T cell epitopes) are identified directly from patients' inflamed synovial tissue, synovial fluid mononuclear cells (SFMCs), or peripheral blood mononuclear cells (PBMCs) by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and tested for immunogenicity using patients' samples (19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because of a limited number of cells, we did not include the testing of irrelevant control peptides in these experiments. However, we have previously shown that patients with RA do not have reactivity to peptides derived from endothelial cell growth factor (ECGF) or MMP-10 peptides (21,23). These autoantigens in LA are irrelevant in RA.…”
Section: Introductionmentioning
confidence: 99%
“…некоторых больных инициирует аутоиммунный процесс с образованием аутоантител к ДНК и цен-тромерной области хромосом, что также может способствовать их аномальному расхождению при делении клетки [15]. Известно, что группа ферментов глутатион-S-трансферазы, кодируемых генами GSTM1 и GSTT1, выполняют роль антиоксидантов, приводя-щих к снижению числа клеток с цитогенетически-ми нарушениями.…”
Section: результаты и обсуждениеunclassified